2020
DOI: 10.1002/ijgo.13257
|View full text |Cite
|
Sign up to set email alerts
|

A bundled intervention lowers surgical site infection in hysterectomy for benign and malignant indications

Abstract: Objective: To evaluate the impact of a surgical site infection (SSI) prevention bundle on SSI rates after hysterectomy for benign and malignant indications at an urban academic medical center. Methods: The bundled invention was implemented for all abdominal gynecologic sur

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…At one academic medical center, the incidence of SSIs after hysterectomy decreased from 4.51% before implementation of a bundle to 1.87% after implementation ( P = .001) 26 . At another academic medical center, the SSI rate after hysterectomy dropped from 2.7% before bundle implementation to 0.4% after implementation (odds ratio = 7.41; 95% confidence interval, 1.67 to 32.75) 27 . At a third academic medical center, interdisciplinary team members recognized that the SIR associated with hysterectomies was 3.5.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At one academic medical center, the incidence of SSIs after hysterectomy decreased from 4.51% before implementation of a bundle to 1.87% after implementation ( P = .001) 26 . At another academic medical center, the SSI rate after hysterectomy dropped from 2.7% before bundle implementation to 0.4% after implementation (odds ratio = 7.41; 95% confidence interval, 1.67 to 32.75) 27 . At a third academic medical center, interdisciplinary team members recognized that the SIR associated with hysterectomies was 3.5.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results of several QI projects reflect improved SSI rates after implementing SSI‐prevention bundles 26‐29 . At one academic medical center, the incidence of SSIs after hysterectomy decreased from 4.51% before implementation of a bundle to 1.87% after implementation ( P = .001) 26 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guo et al [16] (2020) found that 515 hysterectomies in the same period before bundle implementation representing a decrease in SSI rate from 2.7% to 0.4% (odds ratio, 7.41; 95% confidence interval, 1.67-32.75). The two SSIs in the post-bundle period occurred in open hysterectomies, whereas 8 (57.1%) SSIs in the pre-bundle period occurred in minimally invasive hysterectomies.…”
Section: Distribution Of Mean Age Bmi Operation Duration and Hospital...mentioning
confidence: 99%
“…Gillispie-Bell (46) defines normothermia as a core temperature of at least 36˚C measured immediately on the post-anesthesia care unit. A gynaecology-specific 'bundle' has been assessed in other studies that found a reduction in the SSI rate from 1.3 to 0.5% in patients undergoing hysterectomies (43,(46)(47)(48). Implementing surgical 'bundles' is a multidisciplinary effort involving physicians (both gynaecologists and anaesthesiologists), nurses and patients (43).…”
Section: Surgical 'Bundles'mentioning
confidence: 99%
“…Implementing surgical 'bundles' is a multidisciplinary effort involving physicians (both gynaecologists and anaesthesiologists), nurses and patients (43). The gynaecology-specific 'bundle' is extrapolated from general surgery 'bundles' on the basis of existing evidence and best practice guidelines and includes: Wipes with chlorhexidine gluconate; hair removal; preoperative warming (forced-air warming devices); skin preparation (abdominal and, specifically, vaginal preparation); change gloves before closing fascia; sterile dressing; intraoperative normothermia; antimicrobial prophylaxis; and monthly meetings to assess feedback (43,47,48). Moving forward in the SSI prevention with evidence-based 'surgical bundles' that are rapidly covering all surgical fields (4), OG departments should take into consideration the main prevention methods to build 'bundles' in reducing SSI.…”
Section: Surgical 'Bundles'mentioning
confidence: 99%